Crisis of the Mythological? The Melting of the Polar Ice in Greenland in Alfred Döblin’s Berge Meere und Giganten - Hofmann, Hanna Maria (Nordlit, 2008)
The novel Berge Meere und Giganten was written in 1924. I would like to focus my attention on the 7th book in the novel, whose title is Die Enteisung Grönlands (The Melting of the Polar Ice in Greenland). To begin with, I will give a short summary of what the novel is about. The project to melt Greenland's polar ice forms the culmination of a history of the whole of humanity running from the 20th century all the way until the 27th century. Using all their military and technological might, the heat of the Icelandic volcanoes is captured in solid form and transported by ship to the Arctic. With the help of a gigantic net, this heat is then unloaded on to Greenland, thus melting its ice. Greenland ‘strikes back' however, firstly by casting a magical spell. My central thesis is that Döblin`s Greenland fiction is about the destruction of the myth of Greenland and that this ultimately documents a crisis of the mythological itself.